Bee Venom Soluble Phospholipase A2 Exerts Neuroprotective Effects in a Lipopolysaccharide-Induced Mouse Model of Alzheimer’s Disease via Inhibition of Nuclear Factor-Kappa B - Ham, Hyeon Joo; Han, Ji Hye; Lee, Yong Sun; Kim, Ki Cheon; Yun, Jaesuk; Kang, Shin Kook; Park, YangSu; Kim, Se Hyun; Hong, Jin Tae (Frontiers in Aging Neuroscience, 2019)
Neuroinflammation is important in the pathogenesis and development of Alzheimer’s disease (AD). In the AD brain, microglial activation and upregulation of pro-inflammatory mediators both induce amyloid beta (Aβ) accumulation. Regulatory T cells (Tregs) and nuclear factor-kappa B (NF-κB) signaling have been implicated in AD development through their effects on neuroinflammation and microglial activation. The bee venom soluble phospholipase A2 (bv-sPLA2) enzyme is known to exert anti-inflammatory and anti-immune effects. Here, we investigated the inhibitory effects of bv-sPLA2 on memory deficiency in a lipopolysaccharide (LPS)-induced mouse model of AD. We examined whether bv-sPLA2 (0.02, 0.2, and 2 mg/kg by i.p. injection three times for 1 week) could inhibit neuroinflammation and memory impairment in LPS-treated mice (250 μg/kg by i.p. injection daily for 1 week). We also assessed the effects of bv-sPLA2 administration (0.01, 0.1, and 1 μg/ml) on LPS (1 μg/ml)-treated microglial BV-2 cells. In the LPS-injected mouse brain, sPLA2 treatment rescued memory dysfunction and decreased Aβ levels, through the downregulation of amyloidogenic proteins, and decreased the expression of inflammatory proteins and pro-inflammatory cytokines. Moreover, the LPS-mediated increase in inflammatory protein expression was attenuated bv-sPLA2 treatment in BV-2 cells. Treatment with bv-sPLA2 also downregulated signaling by NF-κB, which is considered to be an important factor in the regulation of neuroinflammatory and amyloidogenic responses, both in vivo and in vitro. Additionally, co-treatment with NF-κB (5 μM) and bv-sPLA2 (0.1 μg/ml) exerted more marked anti-inflammatory effects, compared to bv-sPLA2 treatment alone. These results indicate that bv-sPLA2 inhibits LPS-induced neuroinflammation and amyloidogenesis via inhibition of NF-κB.